Improving team dynamics in an acute older people care unit to improve quality and safety of care - Rachid Akrour; Anja Pattschull; Suzana Stamenkovic; Catherine Courret Gilgen; Alberto Garcia Manjon; Yvan Bourgeois; Joachim Rapin (SAGE Open Medicine)
Introduction: Several studies have demonstrated that the team dynamic among healthcare professionals has an impact on the quality of care, as well as the satisfaction of healthcare team members at work. The Input-Process-Output and Intervention model is one way to structure complex interventions with the aim of improving the team dynamic and evaluating their impact on the healthcare professional team, patients, and the organization. Objective: The objective of the study was to describe the steps and results of a quality improvement project aimed at improving the team dynamic of healthcare professionals in the acute older people care unit of a university hospital and improving outcomes for the healthcare professional team, patients, and the organization. Method: The project was based on the Deming cycle framework (Plan-Do-Check-Act) for improving the quality of care. It consisted of the following steps: (1) Implementation plan with an iterative process; (2) interventions according to the Input-Process-Output and Intervention model; and (3) evaluation of the impact of these interventions. Results: The results demonstrated an improvement in most healthcare professional team outcomes, particularly in terms of satisfaction and absenteeism, as well as organizational outcomes. Patient outcomes were highly satisfactory and relatively stable throughout the process. Conclusion: The integration of a healthcare professional team dynamic improvement model into quality and safety of care processes should be considered to optimize clinical and organizational outcomes.